Situation Report: Romania, 2 May 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Tanzanian President Visits Bucharest New Measures in Regard to Romanian-Bulgarian Economic Co-operation US Congress Asked to Approve Trade Agreement with Romania Co-operation with Austria Economic and Political Relations with Britain Romanian Information Media on the Portuguese Elections Era Socialista on Ideology, the National Problem, and History